Network coding for physical layer secrecy - Tajbakhsh, S; Coon, J; Chen, G (Institute of Electrical and Electronics Engineers, 2018)
Physical layer secrecy is highly costly in terms of achievable data rates if perfect secrecy is considered. However, in many practical systems this level of secrecy is not required. In this paper, we introduce a secrecy system based on network coding and physical layer secrecy which is throughput efficient while maintaining a practical level of secrecy. In this system, a set of linear combinations of the original messages are protected with a physical-layer secrecy scheme and another set of linear combinations are freely transmitted over the wireless broadcast channel. This will allow the designer to tune the system for a desired level of secrecy and throughput. We discuss three variants of this coding scheme; The first two use random linear network codes (RLNC) and hence, highly efficient in terms of throughput. The third variant is based on instantly decodable network codes (IDNC) and designed for delay sensitive applications.